Introducing Audio Describer Training in University Interpreting Classes. (May 2022) - Yan, Jackie Xiu; Luo, Kangte
Audio description (AD), the rendering of images into words, helps people who are visually impaired to access audiovisual products. Being able to access media is a basic human right. The United Nations Convention on the Rights of Persons with Disabilities clearly states that people with disabilities should have "access to television programs, films, theater, and other cultural activities, in accessible formats" (United Nations, 2006). Recent developments in technology, for example, text-to-speech synthesizers, have enabled audio description to include more languages (see Tor-Carroggio, 2020). Training is important to ensure the quality of audio describers. Offering audio description training in universities can provide students an opportunity to get early exposure to this field and increase their understanding of the issues about accessibility. This report presents an audio description training module conducted in a university interpreting program in Hong Kong. Based on the commonalities between audio description and interpreting in quality assessment, a set of criteria was proposed and applied to the assessment of the students' audio description performance. A visually impaired colleague was invited to participate in the evaluation, and her timely feedback for the student was provided from the user's perspective. A post-class survey was conducted after the training program. The survey results suggested that students were highly motivated to learn audio description in interpreting classes. In reflecting on the skills cultivated during the training process, students acknowledged the value of audio description training for learning interpreting. The implementation of audio description training in interpreting programs has proved to be feasible and highly regarded by the students. The present study hopes to shed some light on the feasibility of offering audio description training in universities in general and interpreting classes in particular. It is expected this practice can significantly enrich and broaden the scope of education, audio description and development.